Toward a Science of Human Rights - Fuertes-Planas Aleix, Cristina (Historia y Comunicación Social, 2014)
To ask oneself about the possibility of a science of human rights does not constitute a superficial question. Contrariwise, it means the possibility of discovering a methodical study, systematic, a tracking through the length of its history, institutions, guarantees, means of protection, a hierarchy of the same, the possibility of implementation worldwide, the creation of an ethos and a culture of human rights. It is not an easy mission, and clashes with numerous difficulties since its definition is ambiguous, its goal uncertain and unsure, and upon it converge many disciplines; its methodology is not unique but rather multifaceted. Nevertheless, the attempt is worthwhile, particularly to obtain its better dissemination and acceptance, particularly at a moment like the present when multiple structural, political, economic and ideological dangers threaten to destroy the victories obtained gradually over the passage of the decades.
Keywords: Science; human rights; method; culture.